Plant growth-promoting rhizobacteria from vegetable-cultivated soils in Namakkal district: Isolation, characterization and biocontrol potential - Naveen, Banu M; Ezhlilarasu, A (Plant Science Today, 2025)
This study investigated plant growth promoting rhizobacteria (PGPR) isolated from soil samples collected across 5 villages in Namakkal district, a region known for cereal and vegetable cultivation, with the aim of evaluating their plant growth promoting (PGP) traits and biocontrol potential as sustainable alternatives to agrochemicals. A total of 21 bacterial isolates were obtained and screened for key PGP traits, including indole-3-acetic acid (IAA) and ammonia (NH3) production, hydrogen cyanide (HCN) production, phosphate solubilization (PS), nitrogen fixation (NF) and enzymatic activities (amylase, protease and cellulase), while antagonistic activity against Xanthomonas sp. was also assessed. Identification by 16S rRNA sequencing revealed that an unclassified isolate belonged to Bacillus paramycoides, which exhibited all positive PGP traits and demonstrated strong antagonistic activity against Xanthomonas sp. Molecular docking further showed that IAA had a binding affinity of -6.6 kcal/mol with the Xanthomonas sp. (6K62) protein, indicating antimicrobial potential. These findings highlight the application of PGPR, particularly B. paramycoides, in improving soil fertility, enhancing plant growth and providing biocontrol against phytopathogens, thereby reducing reliance on chemical fertilizers and pesticides.